Fibre Bragg grating interrogator design using silicon photonics technology - Lee, Mandy Alexius Si Hui (2019)
There is an increasingly high demand in the need of integrations of technologies to reduce the size of sensors and measurement techniques. Silicon photonics has provided a cheaper and compact alternative to complex structures in data communication. In this project, research is done on spectroscopy to reduce the system to a handheld application. Spectroscopy uses the electromagnetic spectrum to interact with the test samples. It provides a non-destructive method to sense these samples. Near-Infrared Spectroscopy have seen emerging in the markets especially for handheld applications. With the use of the silicon photonics it can help reduce the size. Further research is also done on multi-core fibre optics to transmit the signals. Fibre optics are tested compatible with silicon which give an advantage to this technology in this project.